2020
DOI: 10.3389/fneur.2020.00627
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing Demyelinating Syndromes in Children: A Practical Review of Neuroradiological Mimics

Abstract: Relapsing demyelinating syndromes (RDS) in children encompass a diverse spectrum of entities including multiple sclerosis (MS) acute disseminated encephalomyelitis (ADEM), aquaporin-4 antibody associated neuromyelitis optica spectrum disorder (AQP4-NMOSD) and myelin oligodendrocyte glycoprotein antibody disease (MOG-AD). In addition to these, there are "antibody-negative" demyelinating syndromes which are yet to be fully characterized and defined. The paucity of specific biomarkers and overlap in clinical pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…Optic neuritis associated with MOG antibody is often longitudinally extensive and bilateral, involving the optic discs and sparing the optic chiasm. 1,2,3 The presence of MOG antibody, particularly persistent high titers, in children with an ADEM-like presentation increases the risk of a recurrent/relapsing course, as illustrated by this case. 2,3,4 Conflict of Interest None declared.…”
Section: Accepted Manuscriptmentioning
confidence: 83%
“…Optic neuritis associated with MOG antibody is often longitudinally extensive and bilateral, involving the optic discs and sparing the optic chiasm. 1,2,3 The presence of MOG antibody, particularly persistent high titers, in children with an ADEM-like presentation increases the risk of a recurrent/relapsing course, as illustrated by this case. 2,3,4 Conflict of Interest None declared.…”
Section: Accepted Manuscriptmentioning
confidence: 83%
“…Imaging findings regarding HLH in the central nervous system range from normal findings, to nonspecific findings such as isolated cortical atrophy, to extensive parenchymal disease with multifocal white matter lesions with or without leptomeningeal and/or perivascular enhancement, with frequent cerebellar involvement (7,8,10,11). Tumefactive lesions, optic neuritis and spinal cord lesions have also been described (12). Malik et al grouped imaging patterns into two main groups: 1) parenchymal disease, and 2) normal or nonspecific findings, and subdivided the first group into: 1.1) multifocal cerebral/cerebellar lesions, 1.2) brainstem predominant pattern (CLIPPERS-like pattern), and 1.3) diffuse cerebellar involvement/cerebellitis (11).…”
Section: Discussionmentioning
confidence: 99%
“…This study found that underdiagnosis of NMOSD is still a common problem which may be associated with many factors. The literature describes cases of imitation of NMOSD by other diseases [ 20 , 21 ], also in children [ 22 ]. Perhaps, the complexity of the diagnostic process may be a problem as well as the long time period from the appearance of the first symptom to diagnosis of NMOSD, as has already been described for MS [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%